PENGARUH PAJAK, MEKANISME BONUS, UKURAN PERUSAHAAN, KEPEMILIKAN ASING, TUNNELING INCENTIVE DAN EXCHANGE RATE TERHADAP TRANSFER PRICING (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Asmida, Asmida; Edfan, Darlis; Al, L Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study was to examine the effect of taxes, bonus mechanisms, firm size, foreign ownership, tunneling incentive and exchange rate to transfer pricing at mining companies listed on the Indonesia Stock Exchange in 2016-2018. The data used in this research ini secondary data, namely from annual financial reports. These samples were obtained by purposive sampling method, using several criteria in order to obtain a sample of 19 companie and measure the transfer pricing with the transacsional net margin profit method. Hypothesis testing is done by multiple regression analysis with SPSS ver. 25.0. The results shows that tax have significant effect on transfer pricing at 0.001 <0.05 level of significance, foreign ownership have significant effect on transfer pricing at 0.001 <0.05 level of significance, tunneling incentive have significant effect on transfer pricing at 0.033 <0.05 level of significance, exchange rate have significant effect on transfer pricing at 0.000 <0.05 level of significance, bonus mechanism doesn’t take ani effect on transfer pricing at 0514>005 level of significance and firm size doesn’t take any effect on transfer pricing 0.384> 0.05 level of significance. The amount of determination (r2 ) of the tax effect, the mechanism of bonus, firm size, foreign ownership, tunneling incentive and exchange rate to transfer pricing that is equal to 49% while the remaining 51% is influenced by other variables not examined in this study.Keywords : Taxes, Mechanism Bonus, Firm Size, Foreign Ownership, Tunneling Incentive, Exchange Rate and Transfer Pricing